SYM1 Is the Stress-Induced Saccharomyces cerevisiae Ortholog of the Mammalian Kidney Disease Gene Mpv17 and Is Required for Ethanol Metabolism and Tolerance during Heat Shock - Trott, Amy (American Society for Microbiology, 2004)
Organisms rapidly adapt to severe environmental stress by inducing the expression of a wide array of heat shock proteins as part of a larger cellular response program. We have used a genomics approach to identify novel heat shock-induced genes in Saccharomyces cerevisiae. The uncharacterized open reading frame (ORF) YLR251W was found to be required for both metabolism and tolerance of ethanol during heat shock. YLR251W has significant homology to the mammalian peroxisomal membrane protein Mpv17, and Mpv17(−/−) mice exhibit age-onset glomerulosclerosis, deafness, hypertension, and, ultimately, death by renal failure. Expression of Mpv17 in ylr251wΔ cells complements the 37°C ethanol growth defect, suggesting that these proteins are functional orthologs. We have therefore renamed ORF YLR251W as SYM1 (for “stress-inducible yeast Mpv17”). In contrast to the peroxisomal localization of Mpv17, we find that Sym1 is an integral membrane protein of the inner mitochondrial membrane. In addition, transcriptional profiling of sym1Δ cells uncovered changes in gene expression, including dysregulation of a number of ethanol-repressed genes, exclusively at 37°C relative to wild-type results. Together, these data suggest an important metabolic role for Sym1 in mitochondrial function during heat shock. Furthermore, this study establishes Sym1 as a potential model for understanding the role of Mpv17 in kidney disease and cardiovascular biology.